Shorter Telomeres in Peripheral Blood Mononuclear Cells from Older Persons with Sarcopenia: Results from an Exploratory Study - Marzetti, Emanuele; Lorenzi, Maria; Antocicco, Manuela; Bonassi, Stefano; Celi, Michela; Mastropaolo, Simona; Settanni, Silvana; Valdiglesias, Vanessa; Landi, Francesco; Bernabei, Roberto; Onder, Graziano (Frontiers in Aging Neuroscience, 2014)
Background. Telomere shortening in peripheral blood mononuclear cells (PBMCs) has been associated with biological age and several chronic degenerative diseases. However, the relationship between telomere length and sarcopenia, a hallmark of the aging process, is unknown. The aim of the present study was therefore to determine whether PBMC telomeres obtained from sarcopenic older persons were shorter relative to non-sarcopenic peers. We further explored if PBMC telomere length was associated with frailty, a major clinical correlate of sarcopenia. Methods. Analyses were conducted in 142 persons aged >/= 65 years referred to a geriatric outpatient clinic (University Hospital). The presence of sarcopenia was established according to the European Working Group on Sarcopenia in Older People criteria, with bioelectrical impedance analysis used for muscle mass estimation. The frailty status was determined by both the Fried’s criteria (physical frailty, PF) and a modified Rockwood’s frailty index (FI). Telomere length was measured in PBMCs by quantitative real-time polymerase chain reaction according to the Telomere/Single copy gene ratio (T/S) method. Results. Among 142 outpatients (mean age 75.0 ± 6.5 years, 59.2% women), sarcopenia was diagnosed in 23 individuals (19.3%). The PF phenotype was detected in 74 participants (52.1%). The average FI score was 0.46 ± 0.17. PBMC telomeres were shorter in sarcopenic subjects (T/S = 0.21; 95% CI: 0.18 – 0.24) relative to non-sarcopenic individuals (T/S = 0.26; 95%: CI: 0.24 – 0.28; p = 0.01), independent of age, gender, smoking habit, or comorbidity. No significant associations were determined between telomere length and either PF or FI. Conclusion. PBMC telomere length, expressed as T/S values, is shorter in older outpatients with sarcopenia. The cross-sectional assessment of PBMC telomere length is not sufficient at capturing the complex, multidimensional syndrome of frailty.